2012
DOI: 10.1021/ef201234j
|View full text |Cite
|
Sign up to set email alerts
|

ReaxFF Reactive Force Field for Molecular Dynamics Simulations of Lignite Depolymerization in Supercritical Methanol with Lignite-Related Model Compounds

Abstract: To investigate the detailed mechanisms for lignite methanolysis, we used ReaxFF reactive force field to perform a series of molecular dynamics simulations (MDSs) on a unimolecular model compound. The α-O-4 and β-O-4 types of lignite-related model compounds were selected as representatives of linkages in lignites. The reaction products predicted by ReaxFF MDSs are consistent with those from experimental results reported. The initiation reaction observed in ReaxFF MDSs involving the ether linkage cleavage and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 43 publications
(63 reference statements)
0
10
0
Order By: Relevance
“…For these reasons we employed classical molecular dynamics (MD) methods to model combustion reactions in supercritical conditions. In the first paper of this series we established that the H/C/O parametrization of ReaxFF force field (which is used by other groups to simulate oxy-fuel combustion and supercritical environment) does not reproduce the pressure–density curves for neither H 2 O, nor CO 2 fluids. Reparameterization is required, which distorts reactive potential surfaces considerably.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons we employed classical molecular dynamics (MD) methods to model combustion reactions in supercritical conditions. In the first paper of this series we established that the H/C/O parametrization of ReaxFF force field (which is used by other groups to simulate oxy-fuel combustion and supercritical environment) does not reproduce the pressure–density curves for neither H 2 O, nor CO 2 fluids. Reparameterization is required, which distorts reactive potential surfaces considerably.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al 25 studied the pyrolysis process of perfluorinated ketones at different temperatures (300–5000 K) by using ReaxFF. Salmon et al, 26 Yan et al, 27 and Chen et al 28 used ReaxFF to study the pyrolysis and oxidation of lignite. Xu et al 29 used the ReaxFF-MD simulation method to study the characteristics of lignite pyrolysis products, main element transformation behavior, and pyrolysis mechanism from the perspective of clean utilization at 1600–3000 K. Zheng et al 30 used the ReaxFF molecular dynamic method to study the product distribution and initial chemical reaction of Liulin coal during pyrolysis at 1000–2600 K. Gao et al 31 discussed the dynamic migration mechanism of organic oxygen in the coal pyrolysis process by the ReaxFF molecular dynamic method.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of force field (e.g., ReaxFF, firstly carried out by van Duin [13]) and software (e.g., Material studio, VASP, Gaussian), the molecular simulation methods have frequently been used to obtain the reaction mechanism of chemical substances pyrolysis, such as triglyceride [14,15], ndodecane [16], coal pyrolysis [17][18][19], which is an approach closer to real world process. ReaxFF MD simulation has been affirmed successfully to describe the molecular process underlying the kinetics in pyrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Further investigation of coal pyrolysis is helpful to the vitrinite pyrolysis mechanism. MD simulation was also used for a unimolecular model compound and the Hatcher lignite model by Chen et al [18,29]. Moreover, Zhang et al [30], reported the reaction mechanism of coal pyrolysis and hydrogen production, and concluded that the water clusters in SCW weaken the C-C bonds in aromatic rings.…”
Section: Introductionmentioning
confidence: 99%